Low-density cement paste system for preventing casing deformation of shale gas well and preparation method of low-density cement paste system
By using a low-density cement slurry system in shale gas wells, using buffer materials to crush them in cement stones, alleviating the deformation of the casing by formation pressure, solving the problem of high shale gas well sleeve variability, and achieving the improvement of cement stone strength and cement safety.
Patent Information
- Application Number
- CN202311417490.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The variability of shale gas well sleeves is still very high, and it is difficult for the existing technology to effectively solve this problem.
A low-density cement slurry system for preventing sheathing of shale gas wells is adopted. The system includes oil well cement, buffer materials (such as hollow glass microbeads), microsilicon, premature strength agent, dispersant, suspension agent, water reduction agent, retarder and water. The buffer materials with different pressure bearing capacity are crushed in cement stone to alleviate the deformation of the casing by formation pressure.
It effectively solves the problem of sheathing caused by formation pressure on casing deformation, provides cement slurry with an applicable density range of 1.40g/cm3 to 1.70g/cm3, with excellent comprehensive performance, meets the standards for cementing, meets the cementing needs, and improves the cementing safety and quality of shale gas wells.
Smart Images

Figure CN119912197A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas well cementing engineering, and in particular to a low-density cement slurry system for preventing casing deformation in shale gas wells and a preparation method thereof. Background Art
[0002] The shale gas industry has played an important role in promoting economic and social development, ensuring energy supply and national energy security. However, in the existing shale gas well exploitation process, shale gas well casing deformation is relatively common. Shale gas horizontal well casing deformation is manifested as necking caused by external squeezing or shearing, which is basically characterized as shale layer sliding along weak surfaces such as faults, cracks, and bedding. The source power is the two modes of shale layer uplift and weak surface sliding caused by fracturing fluid injection. Among them, the shale layer expansion / uplift-induced casing deformation mode is manifested as a large amount of fracturing fluid and proppant entering the formation, the formation expands and rises, resulting in natural fractures or interlayer sliding causing shear casing deformation. At the same time, due to the different arch radius when the formation is lifted, interlayer sliding occurs, causing casing deformation.
[0003] The casing deformation mode caused by shale fracture / fault slip is as follows: when the formation expands / uplifts, it encounters natural fractures. When the shear force reaches the critical value, it will stimulate the sliding of the natural fractures, causing casing deformation. In this process, if fracturing fluid enters the natural fractures, the pore pressure in the fractures will increase, the fracture stick-slip coefficient will decrease, and it will be easier to stimulate the sliding of the natural fractures, which will aggravate the casing deformation. Casing deformation mainly occurs in the middle and rear parts of the fracturing section, in formations with fractures / faults and lithological interfaces / stratification, and in formations with excellent cementing quality. Among them, the excellent cementing quality rate is significantly positively correlated with casing deformation.
[0004] At present, some researchers at home and abroad have proposed a series of countermeasures and suggestions to prevent casing changes in shale gas wells, including: increasing the thickness and strength of the casing wall, optimizing the performance of cement stone, etc. However, the casing change rate is still very high, and practice shows that increasing the strength of the casing (thick-walled casing, double-layer casing, etc.) has little effect on alleviating casing damage caused by rock slip. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the casing change rate of current shale gas wells is still very high. The purpose is to provide a low-density cement slurry system for preventing casing change in shale gas wells and a preparation method thereof, thereby solving the problem of high casing change rate in current shale gas wells.
[0006] The present invention is achieved through the following technical solutions:
[0007] On the one hand, the present application provides a low-density cement slurry system for preventing casing deformation in shale gas wells, which includes the following raw materials by weight:
[0008] 100 parts of oil well cement, 10-33 parts of buffer material, 0-15 parts of microsilica, 0-3 parts of early strength agent, 0-2 parts of dispersant, 0-2 parts of suspending agent, 2-6 parts of fluid loss reducer, 0-2 parts of retarder, and 41-46 parts of water.
[0009] Furthermore, the buffer material comprises hollow glass microspheres, and more than 90% of the hollow glass microspheres have a particle size of ≤65 μm.
[0010] Furthermore, the actual density of the hollow glass microspheres is 0.58 g / cm 3 ~0.62g / cm 3 , the bulk density is 0.29g / cm 3 ~0.34g / cm 3 , the compressive strength is 25MPa~82MPa.
[0011] Furthermore, the particle size of the micro-silicon is 0.1 μm to 100 μm, wherein the SiO2 content is ≥ 90%.
[0012] Furthermore, the early strength agent is prepared by mixing CaO, K2SiO3, NaSO4 and NaOH, wherein the mass ratio of CaO, K2SiO3, NaSO4 and NaOH is 30:20:25:25.
[0013] Furthermore, the dispersant includes sulfonated formaldehyde-acetone condensate.
[0014] Furthermore, the suspending agent is a 2-acrylamide-2-methylpropane sulfonic acid polymer thickening material.
[0015] Furthermore, the precipitation agent is polymerized from 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, N,N-dimethylacrylamide, N-vinyl pyrrolidone and microcrystalline cellulose.
[0016] Furthermore, the retarder is polymerized from itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and vinyl phosphoric acid.
[0017] On the other hand, the present application provides a method for preparing a low-density cement slurry system for preventing casing deformation in shale gas wells, comprising the following steps:
[0018] Take oil well cement, buffer material, microsilicon, early strength agent, dispersant and suspending agent according to weight, mix and stir evenly to obtain a dry mix;
[0019] Take a fluid loss reducer, a retarder and water in quantities by weight, mix and stir evenly to obtain slurry water;
[0020] The dry mix is added into the slurry preparation water, mixed and stirred evenly, so as to obtain a low-density cement slurry system for preventing casing deformation in shale gas wells.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] The cement slurry system of the present invention incorporates buffer materials with different pressure bearing capacities into the cement slurry system. The buffer materials in the cement stone are crushed by the external formation pressure, which effectively solves the problem of casing deformation caused by formation pressure. The applicable density range is 1.40g / cm 3 ~1.70g / cm 3 The density range is adjustable, the comprehensive performance is excellent, the cement stone strength meets the standard, and it meets the needs of cementing. At the same time, it can solve the problems of weak formation pressure bearing capacity of shale gas wells, narrow density safety window, and high leakage risk. It provides safety and quality assurance for cementing construction and provides technical support for the efficient development and production of shale gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0024] Figure 1 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 1 of the present invention;
[0025] Figure 2 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 2 of the present invention;
[0026] Figure 3 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 3 of the present invention;
[0027] Figure 4 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 4 of the present invention;
[0028] Figure 5 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 5 of the present invention;
[0029] Figure 6 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 6 of the present invention;
[0030] Figure 7 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 7 of the present invention;
[0031] Figure 8 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Example 8 of the present invention;
[0032] Fig. 9 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 1 of the present invention;
[0033] Fig.10 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 2 of the present invention;
[0034] Fig.11 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 3 of the present invention;
[0035] Fig.12 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 4 of the present invention;
[0036] Fig.13 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 5 of the present invention;
[0037] Fig.14 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 6 of the present invention;
[0038] Fig.15 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 7 of the present invention;
[0039] Fig.16 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Example 8 of the present invention;
[0040] Fig.17 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Comparative Example 1 of the present invention;
[0041] Fig.18 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Comparative Example 2 of the present invention;
[0042] Fig.19 This is a thickening test curve diagram of a low-density cement slurry system for preventing casing change in a shale gas well in Comparative Example 3 of the present invention;
[0043] Fig. 20This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Comparative Example 1 of the present invention;
[0044] Fig.21 This is a test diagram of the elastic modulus of a low-density cement slurry system for preventing casing deformation in a shale gas well in Comparative Example 2 of the present invention;
[0045] Fig. 22 This is a test diagram of the elastic modulus of a low-density cement slurry system used to prevent casing deformation in a shale gas well in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0047] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment provides a low-density cement slurry system for preventing casing change in shale gas wells, with a preparation density of 1.40 g / cm 3 The cement slurry system comprises 100 parts of oil well cement, 33 parts of hollow glass microspheres, 15 parts of microsilica, 2 parts of early strength agent, 0.5 parts of sulfonated formaldehyde-acetone condensate, 2 parts of 2-acrylamide-2-methylpropane sulfonic acid, 6 parts of fluid loss reducer, 1 part of retarder and 47.5 parts of water.
[0050] Among them, more than 90% of the hollow glass microspheres have a particle size of ≤65μm, and the true density of the hollow glass microspheres is 0.58g / cm 3 , the bulk density is 0.29g / cm 3 , the compressive strength is 25MPa.
[0051] Among them, the particle size of microsilicon is 0.1μm and the content of SiO2 is 90%.
[0052] Among them, the early strength agent is prepared by mixing CaO, K2SiO3, NaSO4 and NaOH, and the mass ratio of CaO, K2SiO3, NaSO4 and NaOH is 30:20:25:25.
[0053] The fluid loss reducer is prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC), wherein the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC) is 1:0.9:0.2:0.1:0.1.
[0054] The retarder is polymerized from itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid. The mass ratio of itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid is 20:53:8
[0055] The preparation method of the low-density cement slurry system for preventing casing change in shale gas wells is as follows:
[0056] (1) Weighing oil well cement, hollow glass microspheres, early strength agent, sulfonated formaldehyde-acetone condensate, and 2-acrylamide-2-methylpropane sulfonic acid according to the above amounts, stirring and mixing uniformly to obtain a dry mix;
[0057] (2) Weigh the precipitation agent, retarder and water according to the above amounts, stir and mix them evenly to obtain slurry water;
[0058] (3) Add the dry mixture in step (1) to the water in step (2), mix and stir evenly to obtain a low-density cement slurry system for preventing casing deformation in shale gas wells.
[0059] Example 2
[0060] This embodiment provides a low-density cement slurry system for preventing casing change in shale gas wells, with a preparation density of 1.50 g / cm 3 The cement slurry system includes 100 parts of oil well cement, 22 parts of hollow glass microspheres, 10 parts of microsilica, 1 part of early strength agent, 1 part of sulfonated formaldehyde-acetone condensate, 1.5 parts of 2-acrylamide-2-methylpropane sulfonic acid, 4.5 parts of fluid loss reducer, 1 part of retarder, and 45 parts of water.
[0061] Among them, more than 90% of the hollow glass microspheres have a particle size of ≤65μm, and the true density of the hollow glass microspheres is 0.60g / cm 3 , bulk density is 0.31g / cm 3 , the compressive strength is 40MPa.
[0062] Among them, the particle size of microsilicon is 10μm and the content of SiO2 is 91%.
[0063] Among them, the early strength agent is prepared by mixing CaO, K2SiO3, NaSO4 and NaOH, and the mass ratio of CaO, K2SiO3, NaSO4 and NaOH is 30:20:25:25.
[0064] The fluid loss reducer is prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC), wherein the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC) is 1:1.1:0.3:0.15:0.15.
[0065] The retarder is polymerized from itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid. The mass ratio of itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid is 20:53:8
[0066] The preparation method of the low-density cement slurry system for preventing casing change in shale gas wells is as follows:
[0067] (1) Weighing oil well cement, hollow glass microspheres, early strength agent, sulfonated formaldehyde-acetone condensate, and 2-acrylamide-2-methylpropane sulfonic acid according to the above amounts, stirring and mixing uniformly to obtain a dry mix;
[0068] (2) Weigh the precipitation agent, retarder and water according to the above amounts, stir and mix them evenly to obtain slurry water;
[0069] (3) Add the dry mixture in step (1) to the water in step (2), mix and stir evenly to obtain a low-density cement slurry system for preventing casing deformation in shale gas wells.
[0070] Example 3
[0071] This embodiment provides a low-density cement slurry system for preventing casing change in shale gas wells, with a preparation density of 1.60 g / cm 3 The cement slurry system comprises 100 parts of oil well cement, 15 parts of hollow glass microspheres, 10 parts of microsilica, 2 parts of early strength agent, 0.5 parts of sulfonated formaldehyde-acetone condensate, 1 part of 2-acrylamide-2-methylpropane sulfonic acid, 5 parts of fluid loss reducer, 1 part of retarder, and 46 parts of water.
[0072] Among them, more than 90% of the hollow glass microspheres have a particle size of ≤65μm, and the true density of the hollow glass microspheres is 0.62g / cm 3 , bulk density is 0.34g / cm 3 , the compressive strength is 82MPa.
[0073] Among them, the particle size of microsilicon is 30μm and the content of SiO2 is 92%.
[0074] Among them, the early strength agent is prepared by mixing CaO, K2SiO3, NaSO4 and NaOH, and the mass ratio of CaO, K2SiO3, NaSO4 and NaOH is 30:20:25:25.
[0075] The fluid loss reducer is prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC), wherein the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC) is 1:1.0:0.25:0.1:0.15.
[0076] The retarder is polymerized from itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid. The mass ratio of itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid is 20:53:8
[0077] The preparation method of the low-density cement slurry system for preventing casing change in shale gas wells is as follows:
[0078] (1) Weighing oil well cement, hollow glass microspheres, early strength agent, sulfonated formaldehyde-acetone condensate, and 2-acrylamide-2-methylpropane sulfonic acid according to the above amounts, stirring and mixing uniformly to obtain a dry mix;
[0079] (2) Weigh the precipitation agent, retarder and water according to the above amounts, stir and mix them evenly to obtain slurry water;
[0080] (3) Add the dry mixture in step (1) to the water in step (2), mix and stir evenly to obtain a low-density cement slurry system for preventing casing deformation in shale gas wells.
[0081] Example 4
[0082] This embodiment provides a low-density cement slurry system for preventing casing change in shale gas wells, with a preparation density of 1.70 g / cm 3 The cement slurry system comprises 100 parts of oil well cement, 10 parts of hollow glass microspheres, 5 parts of microsilicon, 1.5 parts of sulfonated formaldehyde-acetone condensate, 2 parts of fluid loss reducer, 1 part of retarder, and 41 parts of water.
[0083] Among them, more than 90% of the hollow glass microspheres have a particle size of ≤65μm, and the true density of the hollow glass microspheres is 0.62g / cm 3 , bulk density is 0.34g / cm3 , the compressive strength is 82MPa.
[0084] Among them, the particle size of microsilicon is 100μm and the content of SiO2 is 92%.
[0085] The fluid loss reducer is prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC), wherein the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), N,N-dimethylacrylamide (DMAA), N-vinylpyrrolidone (NVP) and microcrystalline cellulose (MCC) is 1:1.1:0.2:0.15:0.15.
[0086] The retarder is polymerized from itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid. The mass ratio of itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid and vinyl phosphoric acid is 20:53:8
[0087] Example 5
[0088] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, this embodiment does not contain an early strength agent, and the rest is exactly the same as Example 1.
[0089] Example 6
[0090] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, this embodiment does not contain a dispersant, and the rest is exactly the same as Example 1.
[0091] Example 7
[0092] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, this embodiment does not contain a suspending agent, and the rest is exactly the same as Example 1.
[0093] Example 8
[0094] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, this embodiment does not contain a retarder, and the rest is exactly the same as Example 1.
[0095] The performance of the cement slurry systems prepared in Examples 1 to 8 was evaluated.
[0096] The basic performance test and evaluation of cement slurry were carried out according to the national standard GB / T 19139-2015 "Test Methods for Oil Well Cement". The test results are shown in Table 1 below.
[0097] Table 1
[0098]
[0099]
[0100] It can be seen from the above table that the low-density cement slurry system prepared by the preparation method and formula in this application has a fluidity between 20 and 22 except for the formula of Example 6 without adding a dispersant, indicating that the cement slurry has good pumpability. There is no free liquid and the upper and lower density difference is 0, indicating that the cement slurry prepared by the preparation method and formula of this application has good stability. At the same time, the water loss is within 50 ml, and the water loss is well controlled. In summary, the low-density cement slurry system prepared by the preparation method and formula in this application has good performance and meets the performance requirements of cement slurry design in the cementing industry.
[0101] The thickening time, compressive strength and elastic modulus of the cement paste of the cement slurry systems prepared in Examples 1 to 8 were evaluated.
[0102] According to the national standard GB / T 19139-2015 "Test Methods for Oil Well Cement", the cement slurry thickening time, cement stone compressive strength and elastic modulus were tested and evaluated. The test results are shown in Table 2 below. The thickening test curve of the cement slurry system of Example 1 is shown in Figure 1 As shown, the thickening test curve of the cement slurry system of Example 2 is as follows Figure 2 As shown, the thickening test curve of the cement slurry system of Example 3 is as follows Figure 3 As shown, the thickening test curve of the cement slurry system of Example 4 is as follows Figure 4 As shown; the thickening test curve of the cement slurry system of Example 5 is as shown Figure 5 As shown; the thickening test curve of the cement slurry system of Example 6 is as shown Figure 6 As shown; the thickening test curve of the cement slurry system of Example 7 is as shown Figure 7 As shown; the thickening test curve of the cement slurry system of Example 8 is as shown Figure 8 The elastic modulus test diagram of the cement slurry system of Example 1 is shown in FIG. Fig. 9 As shown; the elastic modulus test diagram of the cement slurry system of Example 2 is as shown Fig.10 As shown; the elastic modulus test diagram of the cement slurry system in Example 3 is as shown Fig.11 As shown; the elastic modulus test diagram of the cement slurry system of Example 4 is as shown Fig.12 As shown; the elastic modulus test diagram of the cement slurry system of Example 5 is as shown Fig.13 As shown; the elastic modulus test diagram of the cement slurry system of Example 6 is as shown Fig.14 As shown; the elastic modulus test diagram of the cement slurry system of Example 7 is as shown Fig.15 As shown; the elastic modulus test diagram of the cement slurry system of Example 8 is as shown Fig.16 As shown;
[0103] Table 2
[0104]
[0105]
[0106] It can be seen from Table 2 that the cement slurry system prepared by the preparation method and formula in this application has a thickening time of more than 180 minutes under the conditions of 110°C×80MPa, which meets the requirements of safe pumping. At the same time, the compressive strength of the system is greater than 7MPa in 24 hours and greater than 14MPa in 48 hours. It can be seen that the cement slurry system prepared by the preparation method and formula in this application not only meets the requirements of safe pumping, but also ensures the development of the compressive strength of cement stone. The elastic modulus test results show that the 1.40~1.70g / cm 3 The elastic modulus of the cement slurry system is low, 1.40g / cm 3 The cement slurry system reaches 2.65GPa. While meeting the compressive strength standard, it has good toughness and can alleviate the damage to the casing caused by formation factors to a certain extent.
[0107] Comparative Example 1
[0108] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, this comparative example does not contain hollow glass microspheres, and the rest is exactly the same as Example 1.
[0109] Comparative Example 2
[0110] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, the amount of hollow glass microspheres in this comparative example is 9 parts, and the rest is exactly the same as Example 1.
[0111] Comparative Example 3
[0112] This embodiment provides a low-density cement slurry system for preventing casing deformation in shale gas wells. Compared with Example 1, the amount of hollow glass microspheres in this comparative example is 40 parts, and the rest is exactly the same as Example 1.
[0113] The performance of the cement slurry systems prepared in Comparative Examples 1 to 3 was evaluated.
[0114] The basic performance test and evaluation of cement slurry were carried out according to the national standard GB / T 19139-2015 "Test Methods for Oil Well Cement". The test results are shown in Table 3 below.
[0115] Table 3
[0116]
[0117]
[0118] It can be seen from Table 3 that different amounts of hollow glass microspheres have a great influence on the performance of the cement slurry system. Without changing other conditions, the hollow glass microspheres have the most significant effect on the slurry density. With the increase of the amount of hollow glass microspheres, the fluidity gradually increases and the water loss gradually decreases.
[0119] The thickening time, compressive strength and elastic modulus of the cement paste of the cement slurry systems prepared in Comparative Examples 1 to 3 were evaluated.
[0120] According to the national standard GB / T 19139-2015 "Test Methods for Oil Well Cement", the cement slurry thickening time and the compressive strength and elastic modulus of cement paste were tested and evaluated. The test results are shown in Table 4 below. The thickening test curve of the cement slurry system of Comparative Example 1 is shown in Fig.17 As shown; the thickening test curve of the cement slurry system of Comparative Example 2 is as shown Fig.18 As shown; the thickening test curve of the cement slurry system of Comparative Example 3 is as shown Fig.19 As shown; the elastic modulus test diagram of the cement slurry system of Comparative Example 1 is as shown Fig. 20 As shown; the elastic modulus test diagram of the cement slurry system of Comparative Example 2 is as shown Fig.21 As shown; the elastic modulus test diagram of the cement slurry system of Comparative Example 3 is as follows Fig. 22 As shown;
[0121] Table 4
[0122]
[0123] It can be seen from Table 4 that different amounts of hollow glass microspheres have a great influence on the thickening time of cement slurry and the mechanical properties of cement paste. Without changing other conditions, as the amount of hollow glass microspheres increases, the thickening time gradually increases, and the compressive strength and elastic modulus gradually decrease, but the mechanical properties are all reduced compared to Example 1. The above-described specific embodiments further explain the purpose, technical scheme and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A low-density cement slurry system for preventing casing change in shale gas wells, characterized in that: The following raw materials are included by weight: 100 parts of oil well cement, 10-33 parts of buffer material, 0-15 parts of microsilica, 0-3 parts of early strength agent, 0-2 parts of dispersant, 0-2 parts of suspending agent, 2-6 parts of fluid loss reducer, 0-2 parts of retarder, and 41-46 parts of water.
2. A low-density cement slurry system for preventing casing change in shale gas wells according to claim 1, characterized in that: The buffer material comprises hollow glass microspheres, and more than 90% of the hollow glass microspheres have a particle size of ≤65 μm.
3. A low-density cement slurry system for preventing casing change in shale gas wells according to claim 2, characterized in that: The true density of the hollow glass microspheres is 0.58 g / cm 3 ~0.62g / cm 3 , the bulk density is 0.29g / cm 3 ~0.34g / cm 3 , the compressive strength is 25MPa~82MPa.
4. A low-density cement slurry system for preventing casing change in shale gas wells according to claim 1, characterized in that: The particle size of the micro silicon is 0.1 μm to 100 μm, wherein the SiO2 content is ≥ 90%.
5. A low-density cement slurry system for preventing casing change in shale gas wells according to claim 1, characterized in that: The early strength agent is prepared by mixing CaO, K2SiO3, NaSO4 and NaOH, wherein the mass ratio of CaO, K2SiO3, NaSO4 and NaOH is 30:20:25:
25.
6. A low-density cement slurry system for preventing casing deformation in shale gas wells according to claim 1, characterized in that: The dispersant includes a sulfonated formaldehyde-acetone condensate.
7. A low-density cement slurry system for preventing casing deformation in shale gas wells according to claim 1, characterized in that: The suspending agent is a 2-acrylamide-2-methylpropane sulfonic acid polymer thickening material.
8. The low-density cement slurry system for preventing casing deformation in shale gas wells according to claim 1, characterized in that: The precipitation agent is prepared by polymerization of 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, N,N-dimethylacrylamide, N-vinyl pyrrolidone and microcrystalline cellulose.
9. A low-density cement slurry system for preventing casing deformation in shale gas wells according to claim 1, characterized in that: The retarder is prepared by polymerization of itaconic acid, 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and vinyl phosphoric acid.
10. A method for preparing a low-density cement slurry system for preventing casing deformation in shale gas wells according to any one of claims 1 to 9, characterized in that: The following steps are involved: Take oil well cement, buffer material, microsilicon, early strength agent, dispersant and suspending agent according to weight, mix and stir evenly to obtain a dry mix; Take a fluid loss reducer, a retarder and water in quantities by weight, mix and stir evenly to obtain slurry water; The dry mix is added into the slurry preparation water, mixed and stirred evenly, and a low-density cement slurry system for preventing casing deformation in shale gas wells is obtained.